Do Marketing Strategy and Product Innovation Contribute to the Marketing Performance of Culinary Enterprises? - Muh Yahya; Nurul Mufida; Mahmudatus Sholihah (Indonesian Journal of Business and Entrepreneurship Research, 2024)
This study aims to examine the impact of marketing strategy and product innovation on marketing performance at Rumah Roti store in Makassar. The population consists of buyers on Jalan Toddopuli 10, with a sample of 31 buyers. Data collection methods include literature review, documentation, and questionnaires. The analysis methods used are validity tests, reliability tests, classical assumption tests, linear regression analysis, t-tests, F-tests, and the coefficient of determination (R2). The t-test results show that both marketing strategy and product innovation have a significant impact on marketing performance. The F-test results indicate that these variables simultaneously influence marketing performance. The coefficient of determination reveals that 94.8% of the variance in marketing performance is explained by marketing strategy and product innovation, with the remaining 5.2% attributed to other factors not included in this study, such as product quality and entrepreneurial orientation. The study concludes that market orientation and service quality are critical factors influencing marketing performance at Rumah Roti store. The recommendation is that the store owner should focus more on innovation, market orientation, and service quality to enhance customer attraction to the store.